Measuring Self-perceived Social Health of Iranians; Finding from Iran Social Health Survey - Abachizadeh, kambiz; Omidnia, Soheila; Hajebi, Ahmad; Shekarriz-Foumani, Reza; Mohseni, Maryam; Zamankhani, Fariba (Novelty in Biomedicine, 2017)
Background: The novelty of the study is to measure self-perceived social health of Iranians as one of the main dimensions of health. Materials and Methods: This cross-sectional study was conducted in all provinces of Iran in September 2014 with 10500 participants to measure self-perceived social health on a scale from 33 to 165 arranged in three areas; family, friends and relatives, and community. Area of "family" was measure in a range from 6 to 30; area of "friends and relatives" was from 9 to 45; and area of "community" was from 19 to 95. The psychometrics of scale was examined in separate previous study. Results: From a total of 10500 participants, 10244 fulfilled questionnaire (Response rate= 97.6%). 49.2% of participants were male. Mean of the total social health score was 99.91; area of "family" was 22; area of "friends and relatives" was 27.6; and area of "community" was 51.2. The main factors negatively influences on social health were low house size, unemployment, being divorced or widow and being at the age of 18-30. There was no significant relationship between social health score and educational level. Conclusion: It is magnificently attained that standardized social health rate in the present study was 3.9% lower than the rate has been estimated in comparison to similar previously conducted study in three big cities of Iran, two years earlier. Area of "community" is also the main accountant for this drop. To continue monitoring the social health of Iranians, we recommend conducting the next rounds every 3-5 years.